Investigation of turbulence rotation in limiter plasmas at W7-X with newly installed poloidal correlation reflectometer. (25th April 2017) - Krämer-Flecken, A.; Windisch, T.; Behr, W.; Czymek, G.; Drews, P.; Fuchert, G.; Geiger, J.; Grulke, O.; Hirsch, M.; Knaup, M.; Liang, Y.; Neubauer, O.; et al.
Abstract: For the first operation phase of the optimized stellarator W7-X, a heterodyne poloidal correlation reflectometry diagnostic is installed and put into operation. The system is intended to measure the perpendicular (with respect to the magnetic field) turbulence rotation and turbulence properties, such as the decorrelation time and correlation length at the plasma edge. Furthermore, it can give information on the magnetic field line pitch angle. The system consists of an array of microwave antennas distributed in the poloidal and toroidal directions. The frequency range of 22 GHz–40 GHz allows us to access local plasma densities of 0.6 × 10 19 m −3 – 2.0 × 10 19 m −3 . During the first operation phase the turbulence rotation is measured in almost all plasmas. In addition, the radial electric field is estimated and compared to that in neoclassical theory. The relatively low plasma density allows us to cover up to 80% of the plasma radius during OP1.1. The obtained data cover various experimental programs and are partly presented in the paper.